Experimental Study on River Meander Planform Pattern - Syuhada Yong, Nurul; Noorazurah Mohamad, Irma; Koon Lee, Wei (International Journal of Engineering and Technology, 2018)
River meander basically related with one of the main catastrophe in real scenario such as flood. The number of research on river meander characteristics and process is quite small. Therefore, the study on river meander and its characteristics by using a physical model is one of the methods to enhance the knowledge on it. The main purposes for current study are to determine the characteristics of meandering river and to investigate the lateral movement of the river meander channel bank. The scope of study includes execution of desk study and developing a physical model of river meander by using sand channel in order to understand the behaviors of meandering river. All of the parameters and calculations are investigated through the experimental works. Based on the experimental works, the explanation on the river meander characteristics and planform lateral movement due to the process of erosion and deposition are achieved. Erosion and deposition process give an increment to the initial channel width with respect to the angle of direction Î² and flow rate Q. As a conclusion, this study can give a plenty of information that can act as references to gain more understanding on the river meander planform pattern.Â Â